The Dynamics of Economic Policy and Regional Specialization: Evidence from China's High-tech Industry - Dan Zheng; Tatsuaki Kuroda (European Regional Science Association (ERSA), 2011)
This paper investigates the effects of economic policy on regional specialization of Chinas high-tech industries for the period 1996 to 2005. Results indicate that the average level of regional specialization increases over years. Moreover, high-tech industry sector is highly localized in coastal regions. Using a dynamic panel data approach, we find that the implementation of high technology oriented export policy and subsidies for science and high technology activities encourage regional specialization, whereas local governments protections for local high-tech enterprises impede it. The empirical study also confirms the important role of high-skilled labor in determining regional specialization.
Keywords: 330; economic policy; specialization; high-tech industry; dynamics